Evaluation of Antioxidant and Anti-inflammatory Potential of Alpinia officinarum with Different Ionic Solutions - Nuray Üremiş; Figen Güzelgül; Ergül Belge Kurutaş (Turkish Journal of Agriculture: Food Science and Technology)
Alpinia officinarum, which attracts attention with its antioxidant and anti-inflammatory properties, is used in traditional medicine, especially to relieve stomach and digestive system disorders. Although many studies have revealed the various pharmacological effects of Alpinia officinarum, the effect of different ionic solvents on its biological activities has yet to be investigated. In this study, the effects of homogenization of Alpinia officinarum roots with potassium chloride (KCl), sodium chloride (NaCl), and phosphate (PBS) buffer solutions on the antioxidant and anti-inflammatory properties of the plant were investigated. Alpinia officinarum plant was collected from the Adana region during the season, and fresh root parts were separated and analyzed. Superoxide dismutase (SOD), catalase (CAT), myeloperoxidase (MPO) enzyme activities, and malondialdehyde (MDA) levels of plant homogenates prepared with KCl, NaCl, and PBS were determined by spectrophotometric analysis. The highest MPO and CAT enzyme activities were observed in the KCl solution, while lower levels were observed in NaCl and PBS solutions, respectively. The highest MDA level was observed in the PBS solution. Moreover, SOD enzyme activity showed a decreasing trend in NaCl, KCl, and PBS solutions, respectively. These findings suggest that the biological activity of plant extracts may vary depending on the solvent used. Determination of the conditions under which the antioxidant and anti-inflammatory effects of Alpinia officinarum in different ionic solvents are the highest supports increasing the bioavailability of the plant.